PENGARUH DOSIS BOKASHI BERBASIS CAMPURAN BIOMASSA KIRINYU SERTA BATANG PISANG DAN KONSENTRASI ZAT PENGATUR TUMBUH (ZPT) HORMONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KOL BUNGA (Brassica oleracea var. Botrytis) - Kiuk, Yosni; Arsa, IGB Adwita; Wila, Yeri R.; Nguru, Elias St. O.; Bunga, Widasari; Serangmo, Diana Y. L. (JURNAL AGRISA, 2024)
This research was conducted at the Dryland Laboratory of Nusa Cendana University Kupang from September to December 2022. The purpose of this study was to determine the effect of interaction of doses of solid bokashi fertilizer made from a mixture of kirinyu and banana stem and hormonic concentration on the growth and yield of Cauliflower and determining the combination of those interaction that provides the best growth and yield of Cauliflower plants. This research was a factorial experiment, using Randomized Complete Block Design (RCBD) with three blocks and consisting of nine treatment combinations per blocks. The observed variables were plant height increse (cm), increase in leaves number, increase in stem circumference (cm), gross weight (g) and net weight (g). The observation data were analyzed by analysis of variance (ANOVA) and and followed by DMRT test (significant level 0.05%). The results showed that the interaction between the application of doses of bokashi and hormone concentration significantly affected the increase in height, increase in leaf number, and net fresh weight of cauliflower plants. The combination of treatment doses of bokashi at 10 tons/ha with a hormone concentration of 8 cc/L was the best interaction, with a net fresh weight of cauliflower plants reaching 265.71 g/ plant.